Control and accountability mechanisms in conditional cash transfer programs : a review of programs in Latin America and the Caribbean (World Bank WashingtonUS, 2007)
Assesses the performance of Conditional Cash Transfer (CCT) control and accountability systems in programs supported by the World Bank in Latin America and the Caribbean and to identify areas that may need to be improved.
Keywords: TRANSFER INCOME